The healthy workforce : enhancing wellbeing and productivity in the workers of the future - Bevan, S.; Cooper, Cary L. (The future of work, 2021)
Mental health issues, stress and chronic illness are the biggest causes of absence from work and loss of productivity in most Western economies. Research and public awareness of this epidemic of physical and mental ill-health among working age people is growing, but our understanding of its impact on company performance and productivity and possible solutions for the future is less advanced. The Healthy Workforce: Enhancing Wellbeing and Productivity in the Workers of the Future examines current challenges and future solutions to understand issues around how we can improve the health of today's and tomorrow's workforce. This book will look at why workforce health is such an important challenge for businesses, governments and for employees today and how this will increase in the future with an ageing workforce. Closely linked to the authors' exploration of health issues in the work context is a focus on the impact of worker health on direct and indirect productivity costs. This book offers practical guidance for professionals on getting started in the delivery of an effective and evidence-based workplace health plan which can enhance and sustain productivity growth in business now and for the future.